2022
DOI: 10.1093/cdn/nzac009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Young Australian Adults’ Food Practices

Abstract: Background Young Australian adults exhibit poor food behaviors. These include increased consumption of Energy-Dense, Nutrient-Poor (EDNP) foods, sugar-sweetened beverages, and low consumption of fruit and vegetables. However, little is known about how the coronavirus disease 2019 (COVID-19) pandemic affected young Australian adults’ pre-existing adverse food behaviors. Objectives The present study aimed to understand the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The number of people with significant deficiency declined each year until 2020; but in 2021, the probability of people under 75 years of age having a significant deficiency was higher than in 2019 and 2020. The reason for this rise, and for an even larger rise in the probability of hypovitaminosis C, may be related to changes in diet during COVID‐19 lockdowns, including altered consumption of fresh fruit and vegetables during this period; 22 however, most relevant studies did not take socio‐economic factors into account.…”
Section: Discussionmentioning
confidence: 99%
“…The number of people with significant deficiency declined each year until 2020; but in 2021, the probability of people under 75 years of age having a significant deficiency was higher than in 2019 and 2020. The reason for this rise, and for an even larger rise in the probability of hypovitaminosis C, may be related to changes in diet during COVID‐19 lockdowns, including altered consumption of fresh fruit and vegetables during this period; 22 however, most relevant studies did not take socio‐economic factors into account.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it should be noted that while the survey was open to individuals from both Australia and New Zealand, there were no respondents from New Zealand due to the nature of respondent recruitment, although New Zealand consumer perceptions of nutrition content and health claims has recently been assessed (Stuthridge et al ., 2022). It is worth noting that data collection took place prior to the COVID-19 pandemic, which greatly impacted the food supply and consumer purchasing and consumption behaviours (Godrich et al ., 2022; Kombanda et al ., 2022). Finally, this survey explored self-reported used of nutrition and health claims, which may not reflect actual use of claims during shopping experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Among U.S. adults during the pandemic, similar associations were reported, with drinking more SSBs associated with being younger, having less education, lower household income, and being obese [57] . A qualitative study in young adults in Australia reported replacing meals with beverages or snacks, which may have been a way to manage financial instability and food insecurity [58] . Another study in Norway reported an association between high-sugar foods and beverages in those with psychological distress [59] , but the relationship we detected with psychological distress was no longer significant after adjusting for confounders, which may be due to underreporting of SSBs more broadly [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%